Analisis Faktor Stres Terhadap Asupan Makan Dan Kadar Glukosa Darah Pada Pasien Diabetes Melitus Tipe 2 Pada Masa Pandemi Covid - 19 di Puskesmas Mulyorejo Kota Malang - Anindhita Saviorel Rivaldy; Endang Sutjiati; Dwipajati Dwipajati (NUTRITURE JOURNAL, 2023)
ABSTRACT : Diabetes mellitus is a metabolic disease with characteristic hyperglycemia. The prevalence of type 2 diabetes mellitus based on the results of Riskesdas in 2018 is 2%, which has increased since 2013. High levels of stress can affect food intake. In addition, stress levels are one of the causes of high blood glucose levels. With stress in a person will affect appetite so that it affects food intake. Intake of macronutrients consisting of carbohydrates, proteins, and fats will be converted into glucose in the body. Method :This study uses an analytical observational type of research, using a Cross Sectional approach. Results : The results of the statistical test of the relationship between stress levels and carbohydrate intake have a p value of 0.644 with a correlation coefficient of 0.11, while the relationship between stress levels and protein intake with a p value of 0.584 with a correlation coefficient of 0.130, the relationship between stress levels and fat intake with a p value of 0.705 and correlation coeficient – ??0.03, the result of stress level with blood glucose level with p value 0.705 and correlation coeficient 0.09. Conclusion: There is a significant but not significant relationship between stress levels with food intake and blood glucose levels in Type 2 diabetes mellitus patients.